2020
DOI: 10.3389/fnins.2020.521595
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Time Window of Event-Related Potential Using Multiple-Set Consensus Clustering

Abstract: Clustering is a promising tool for grouping the sequence of similar time-points aimed to identify the attention blocks in spatiotemporal event-related potentials (ERPs) analysis. It is most likely to elicit the appropriate time window for ERP of interest if a suitable clustering method is applied to spatiotemporal ERP. However, how to reliably estimate a proper time window from entire individual subjects' data is still challenging. In this study, we developed a novel multiset consensus clustering method in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Once clustering results were obtained from the individual subjects, a modified version of the time window determination of our previous work (Mahini et al, 2020) was applied for each subject. We modified the time window determination through two criteria in two steps: First, we detected the candidate cluster maps, i.e., the cluster maps with high inner similarity, e.g., > 0.95, in the experimentally interesting interval.…”
Section: Time Window Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Once clustering results were obtained from the individual subjects, a modified version of the time window determination of our previous work (Mahini et al, 2020) was applied for each subject. We modified the time window determination through two criteria in two steps: First, we detected the candidate cluster maps, i.e., the cluster maps with high inner similarity, e.g., > 0.95, in the experimentally interesting interval.…”
Section: Time Window Determinationmentioning
confidence: 99%
“…Other clustering methods such as the Gaussian mixture model for individual subjects (De Lucia et al, 2007b) and single-trial EEG (De Lucia et al, 2007a), and stimulus-related statistical information from single-trial responses (Tzovara, Murray, Plomp, et al, 2012) have been used for EEG data. On the other hand, it has also been shown that consensus clustering can result in consistent and reliable clustering outcomes for biological data (Abu-Jamous et al, 2015;Liu et al, 2017), especially in ERP identification from group-averaged ERP data (Mahini et al, 2020;Mahini et al, 2022). The remaining challenge with the clustering analysis of single-trial EEG is the existing high degree of inconsistency in the EEG data that may lead to uncertain or faulty clustering results.…”
Section: Introductionmentioning
confidence: 99%
“…As for all systems, the final performance relies on the performance of the single parts, as well as on their synergy. One of the key performance parameters for BCIs is the accuracy that can be guaranteed by the system within a reasonable latency window [60,61]. The accuracy obtained depends on the chosen paradigm, on the integrated sensor performance in a band or helmet, and on the performance of the decoder system, i.e.…”
Section: Considerations On the Choice Of Bci Sensorsmentioning
confidence: 99%
“…In order to assess the proposed method, we employed two ERP data, simulated and real data. For the simulated data [31], we test the proposed method against our prior knowledge, i.e., about the spatial and temporal properties of pre-defined ERP components when more noise is added to the data. Likewise, for the real ERP data, we test our method for qualifying the ERP of interest in the prior study [19] when the existing noise in the data increases.…”
Section: Erp Datamentioning
confidence: 99%
“…Despite using GFP and the winner-takes-all strategy in determining template maps in the microstates analysis, as argued in some research [11,55], the second group takes whole time points and polarity into account for clustering of spatio-temporal ERP. Recently, we discussed qualifying ERP of interest using consensus clustering as a reliable method for ERP data in different resolutions [31,32,33]. However, cluster analysis of noisy data can result in many noisy clusters and loss of the main components due to being sensitive to the data quality if inappropriate clustering is applied.…”
Section: Introductionmentioning
confidence: 99%